Stakeholders Alignment in CSR Implementation in Southeast Asian Agro-industry - Sani, Nabila Talitha; Mutiara, Rakyan Sekar Kinanti; Pratama, Kevin Rendra (Global South Review, 2024)
This article focuses on the broader misalignment of Corporate Social Responsibility (CSR) programs by multi-national corporations in Southeast Asia, particularly in the agricultural sector. It explains the likely causes of such impact through the lens of the Stakeholder Theory. The paper aims to illustrate how corporations present and strategize their CSR initiatives, emphasizing that the proposed solutions may only sometimes align with the actual needs of the recipients. Using Freeman's perspective/ This paper argues that an intrinsic disparity exists between the intentions and execution of CSR programs, particularly those initiated by multi-national companies, and the divergence of expectations between corporations acting as implementers and the recipients of these programs. Despite the clear articulation of these requests by most affected locals, multi-national corporations often need help to meet these demands. As a result, the lack of accessible information and limited consumer literacy, coupled with political and commercial branding by ASEAN, creates a conducive environment for CSR misalignments.Keywords: CSR; Southeast Asia; agriculture; stakeholder theory